Experimental Study on the Reliability of an Active Unloading System for Strengthening of Reinforced Concrete Columns - Yongquan Wang; Tianfu Li; Kaifa Dong; Zhengxing Guo; Jing Fu (Advances in Civil Engineering)
In strengthening and retrofitting of reinforced concrete (RC) frame structures, especially in the case of column replacement, unloading of existing columns usually plays an important part in the construction. However, the reliability of the commonly used active unloading system for RC columns can only be evaluated by real-time monitoring of the unloading status during the construction process, which will threaten the safety of the personnel and structures, especially in the case of unloading with large amplitude. In addition, the commonly adopted passive unloading methods are unable to actively control the unloading force. Therefore, an unloading scheme with active control of the unloading process was proposed, and its reliability was experimentally investigated in the present study. According to the requirements of the unloading force, an active unloading self-balancing system using the steel diagonal braces and prestressed steel tie rods was designed for the RC column structure. The vertical load was applied by a hydraulic jack mounted on top of the RC column, and the real-time monitoring data analysis was adopted to verify the feasibility of the active unloading plan and the reliability of the force transmission. The test results indicated that the proposed active unloading control technology is reliable in force transmission.